Analisis Hubungan Technostress Terhadap Kesadaran Keamanan Informasi Pada Guru SMA - Bayu, Airlangga; Setiawan, Bambang (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Technostress is a phenomenon that has recently occurred frequently due to the significant development of information technology. Post COVID 19 pandemic, many sectors have transformed to information technology. As a result, many individuals who feel not fully prepared to use technology feel overwhelmed so they are vulnerable to experiencing technostress. On the other hand, as information technology develops, the risk of information security awareness is also increasingly vulnerable. This can be proven by the increasing number of data leakage cases that occur. This study aims to determine the relationship and influence between technostress and information security awareness. This study adapts three domains from HAIS-Q, namely password management, application use, and email use. This research uses PLS SEM method with 84 respondents. The results of this study prove that technostress related to password management and technostress related to email use have a negative and significant effect on information security awareness. While technostress related to the use of applications has a negative but insignificant effect on information security awareness.